INTERACTION OF Meloidogyne incognita WITH Botryodiplodia theobromae ON Manihot esculenta (CASSAVA) AND ITS BIOCONTROL (2014)
The Root-Knot Nematode (RKN), Meloidogyne incognita and fungus Botryodiplodia theobromae, are important pests that cause yield losses in cassava and other crops. Chemicals have been used to manage these pests but with undesirable side effects. Information on pathogenicity of M. incognita, its interaction with B. theobromae and its biocontrol in Nigeria is very little. Therefore, pathogenicity of M. incognita on cassava, its interaction with B. theobromae and management with biocontrol agents were investigated. A split–plot experiment was conducted in two cropping seasons with nematode-infested and denematised treatments (main-plot) on five cassava cultivars (sub-plots) to study pathogenicity in both field and pots. Two-week old potted sproutings were inoculated with 0, 1000, 10000 eggs of M. incognita per pot in four replicates in a 5 x 3 factorial experiment. Vegetative Growth (VG), galling index and yield-related traits were assessed using standard procedure. Interaction between M. incognita and B. theobromae on cassava was also investigated in pot and microplot field experiments. Two-week old sproutings of TMS 30572, TME 1 and Ofege cassava cultivars were each inoculated with 0, 1000 and 10000 M. incognita eggs, 5x105 spores mL-1 of B. theobromae and combined inoculation of M. incognita+B. theobromae per pot (r=4). Similar treatments were applied to sproutings in the microplots. Plants were assessed for VG, yield, percentage tuber rot and nematode reproduction. The assessment of Glomus mosseae and Paecilomyces lilacinus solely and in combination in the management of M. incognita was evaluated in pot and field studies following standard procedures. Plants were assessed for VG, yield, galling index and nematode reproduction. Data were analysed using descriptive statistics and ANOVA at p=0.05. Meloidogyne incognita reduced by 35.0%, 30%, 18.8%, 54.3% and 53.0% for plant height, shoot weight, stem diameter, fresh tuber weight and number of tubers, respectively. Galling index increased with increase in inoculum density. In the interaction studies, sole inoculation with M. incognita reduced plant height (15.0%), fresh shoot weight (34.9%), number of tubers (35.6%) and tuber weight (32.0%). Inoculation with B. theobromae alone significantly reduced plant height (9.0%), fresh shoot weight (15.7%), number of tubers (22.7%) and tuber weight (25.0%). Combined effects of M. incognita and B. theobromae reduced plant height (25.6%), fresh shoot weight (44.6%), number of tubers (43.2%), tuber weight (72.2%) and increased tuber rot by 48.1% across cultivars. Paecilomyces lilacinus and G. mosseae reduced M. incognita population by 85.0% and 86.7% respectively; and, when added together, by 60.0%. Galling index was reduced by 66.6% and 66.5% respectively when P. lilacinus and G. mosseae were solely applied and when applied together by 35.7%. The use of P. lilacinus and G. mosseae increased VG by 30.4% and 26.7% and tuber weight by 55.9% and 58.3% respectively. Meloidogyne incognita and Botryodiplodia theobromae reduced the growth, yield and quality of cassava. Applications of Paecilomyces lilacinus and Glomus mosseae have great potential in the management of Meloidogyne incognita in cassava production.